PENERAPAN METODE LANGSUNG DALAM MENINGKATKAN KETERAMPILAN BERBAHASA ARAB SISWA KELAS VIII SMP UNISMUH MAKASSAR - Jusniarti Jafar; Fatmawati Fatmawati (Universitas Muhammadiyah Makassar, 2019)
The purpose of this study is to describe the learning process with the direct method of learning Arabic in Makassar Unismuh Middle School and to find out the results of applying the direct method in learning Arabic. This research is a Classroom Action Research (CAR) with several cycles to get the desired data and information.From the results of this study it can be seen that the results of learning Arabic in class VIII Makassar Unismuh Middle School has increased after the implementation of direct methods in learning. This can be seen from the increase in student learning outcomes from the medium category in the first cycle and the high category in the second cycle with an average score of 7.1 increasing to 8.11.Keywords: Direct method, Language, Arabic